Diflavonols as single emitters for polymer-based WOLEDs - Kosach, V.V.; Pivovarenko, V.G.; Yashchuk, V.M. (Functional Materials, 2016)
The spectral peculiarities of polymer/dye solid mixtures on the base of PEPCa polymer (polyepoxypropylcarbazole) as matrix and DFOM (3,7-dihydroxy-2,8-diphenyl-4H,6H-pyrano[3,2-g] chromene-4,6-diones) as emitter were investigated. Peculiarities intramolecular proton transference after the excitation of molecule, incident to this material, allows one to create emitting layer with emission spectrum close to white light and using only one luminophore. Spectral behavior of investigated compounds proves the presence of excitation energy transfer from the PEPCa matrix to the DFOM molecules, which is necessary for effective use of the excitation energy and forming luminescence curve needed. Luminescence of the investigated films demonstrates color characteristics CRI 54 and CIE (0.33, 0.42) which gives a possibility to consider such systems as promising in the context of developing White OLED emitters.